The Moderating Role of Culture on the Performance Effect of Entrepreneurial Orientation in Malaysia - Edward, Oswald Timothy; Candran, VGR (AeU, 2015)
Prior research suggests that entrepreneurial orientation of firms is a key ingredient for organizational success. However, in this era of rapid globalization, national culture could be the distinguishing forces that can significantly affect the performance of both national and international organizations. The purpose of this paper is to propose a framework to assess the entrepreneurial orientation to firm performance relationship and the potential influence of culture. Therefore, national culture can be examined as a potential moderator of the entrepreneurial orientation to performance relationship. This moderating variable may explain some of the discrepancies in the direct performance effects of entrepreneurial orientation in international context. Specifically, this paper attempts to describe what is the state of entrepreneurial orientation in Malaysia; does entrepreneurial orientation influence the business performance of firms in Malaysia; and, to what extent does national culture moderate the effects of entrepreneurial orientations on the business performance of firms in Malaysia. A framework positing an association between the degree of entrepreneurial orientation and performance and an association between national culture and the degree of entrepreneurial orientation is proposed.